The efficacy of using exogenous enzymes cocktail on production, egg quality, egg nutrients and blood metabolites of laying hens fed distiller's dried grains with solubles. Issue 2 (8th October 2017) - Abd El‐Hack, M. E.; Chaudhry, M. T.; Mahrose, K. M.; Noreldin, A.; Emam, M.; Alagawany, M.
Summary: An experiment was performed using 120 Hisex Brown laying hens for evaluating the effects of different inclusion levels of corn distiller's dried grains with solubles (DDGS) as a replacement of soybean meal (SBM) with or without enzyme cocktail on performance, egg quality, egg nutrients and blood metabolites in laying hens through 22–42 weeks of age. A 4 × 2 factorial design experiment was performed including four substitution levels of DDGS (0, 250, 500 and 750 g/kg respectively) and two enzyme cocktail levels (0 and 250 mg/kg diet). The used enzyme in this study "Gallazyme" composed of xylanase, Trichoderma longibrachiatum (600 units/g), protease, Bacillus subtilis (8, 000 units/g) and amylase and Bacillus amyloliquofaciens (800 units/g). The control diet showed the best feed efficiency followed by the intermediate levels of DDGS. The lowest value of feed efficiency was found in the group fed the highest level of DDGS. Enzyme addition improved feed efficiency and decreased laying rate. Increasing DDGS levels was associated with albumin and shell thickness increases. Dietary DDGS depressed all egg components except the organic matter which maximised in enzyme‐treated groups. Increasing DDGS level was accompanied by increase in yolk cholesterol and total lipids. No significant impacts were detected with enzymes supplementation on yolk lipids profile. Excepting serum calcium and phosphorous, all serum constituents increased with increasing level of DDGS. Using enzyme markedly depressed serum ammonia by 15.02% and increased calcium by 6.44% compared with enzyme‐free diets. Interaction between DDGS and enzyme was significant on most of studied parameters. It could be concluded that using enzyme cocktail in DDGS‐based diets may improve feed efficiency and egg quality, in addition to lowering blood ammonia and increasing blood calcium. It is recommended to substitute SBM by DDGS up to 500 g/kg diet.